2021
DOI: 10.1590/1806-908820210000037
|View full text |Cite
|
Sign up to set email alerts
|

Radicular Biomass and Organic Carbon of the Soil in Forest Formations in the Southern Amazonian Mesoregion

Abstract: The soils of the Amazon region, despite being under one of the densest forests in the world, are mostly characterized by the low availability of nutrients, with litter being the main route of nutrient entry. The objective of this study was to quantify the biomass of fine roots in the dry and rainy seasons of the year, including the organic carbon of the soil, and to compare the results in different study environments. The study was carried out in environments of native forest and reforestation aged over 20 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Regarding the decomposition of litter in the Amazon, works developed by Freire et al (2020) in studies of decomposition in 'terra firme' environments in Western Amazon; Pereira et al (2016) evaluating litter and nutrients in 'terra firme' tropical forest in the Amazon basin, as well as Bello et al (2021) who studied decomposition in reforestation and forest systems found that the leaf fraction contributes the most to returning nutrients to the soil. For Tonin et al (2017) the climatic components (high temperature and high atmospheric humidity) of the Amazon assume a determining role in the decomposition of the litter, enabling the development of vegetation without Fertilization and liming were not performed on the areas during the entire growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the decomposition of litter in the Amazon, works developed by Freire et al (2020) in studies of decomposition in 'terra firme' environments in Western Amazon; Pereira et al (2016) evaluating litter and nutrients in 'terra firme' tropical forest in the Amazon basin, as well as Bello et al (2021) who studied decomposition in reforestation and forest systems found that the leaf fraction contributes the most to returning nutrients to the soil. For Tonin et al (2017) the climatic components (high temperature and high atmospheric humidity) of the Amazon assume a determining role in the decomposition of the litter, enabling the development of vegetation without Fertilization and liming were not performed on the areas during the entire growing season.…”
Section: Introductionmentioning
confidence: 99%